2012
DOI: 10.1158/1535-7163.mct-12-0621
|View full text |Cite
|
Sign up to set email alerts
|

Contrary Regulation of Bladder Cancer Cell Proliferation and Invasion by Dexamethasone-Mediated Glucocorticoid Receptor Signals

Abstract: In patients with advanced bladder cancer, glucocorticoids are frequently given to reduce acute toxicity, particularly hyperemesis, during chemotherapy, as well as to improve cachectic conditions. However, it remains unclear whether glucocorticoids directly affect the development and progression of bladder cancer through the glucocorticoid receptor pathway. Glucocorticoid receptor expression was first investigated in human bladder cancer lines and tissue microarrays. Then, the effects of dexamethasone on glucoc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(93 citation statements)
references
References 23 publications
5
85
0
Order By: Relevance
“…To link the above findings to epithelial-to-mesenchymal transition (EMT) implicated in invasion and metastasis of urothelial carcinoma, 18,19 we assessed expression levels of epithelial and mesenchymal markers by western blotting. As shown in Figure 4C, silencing of GATA3 was associated with an increasing level of a mesenchymal marker N-cadherin and a decreasing level of an epithelial marker β-catenin.…”
Section: Decreased Expression Of Gata3 In Bladder Cancer Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…To link the above findings to epithelial-to-mesenchymal transition (EMT) implicated in invasion and metastasis of urothelial carcinoma, 18,19 we assessed expression levels of epithelial and mesenchymal markers by western blotting. As shown in Figure 4C, silencing of GATA3 was associated with an increasing level of a mesenchymal marker N-cadherin and a decreasing level of an epithelial marker β-catenin.…”
Section: Decreased Expression Of Gata3 In Bladder Cancer Linesmentioning
confidence: 99%
“…18 Briefly, cells (1.5 × 10 5 ) in 100 μl of serum-free medium were added to the upper chamber of the transwell, while 600 μl of medium containing 10% FBS was added to the lower chamber. After incubation for 36 h at 37 °C in a CO 2 incubator, invaded cells were fixed, stained with 0.1% crystal violet, and counted under a light microscope.…”
Section: Cell Culture and Chemicalsmentioning
confidence: 99%
“…[6][7][8] We have demonstrated that glucocorticoids directly mediate GR activity in BC cells and strongly inhibit BC cell invasion and metastasis. It is noteworthy, however, that some natural or synthetic glucocorticoids, such as hydrocortisone and dexamethasone, contradictorily promote BC cell proliferation via inhibiting apoptosis particularly that induced by a chemotherapeutic drug cisplatin.…”
Section: Introductionmentioning
confidence: 98%
“…It is noteworthy, however, that some natural or synthetic glucocorticoids, such as hydrocortisone and dexamethasone, contradictorily promote BC cell proliferation via inhibiting apoptosis particularly that induced by a chemotherapeutic drug cisplatin. 6,7 adjacent or separate non-neoplastic urothelial tissue specimens. 9 However, there were only a few studies demonstrating the expression of steroid hormone receptors, such as AR [10][11][12] and ERb, 11 in UUTUCs.…”
Section: Introductionmentioning
confidence: 99%
“…PIP 3 binds to the PH domain of Akt resulting in phosphorylation and activation, which increases cell survival, growth, and metabolism (2,3). Interestingly, glucocorticoids (GCs), which inhibit growth (4) and induce apoptosis in a variety of cells (5), have been shown to increase expression of PTEN in A549 human lung carcinoma cells (6). This suggests that one aspect of the anti-growth properties of GCs may be mediated through the up-regulation of PTEN.…”
mentioning
confidence: 99%